ANALISIS PENGARUH BRAND EXPERIENCE TERHADAP BRAND TRUST DAN DAMPAKNYA PADA CUSTOMER SATISFACTION PRODUK KAOS POLO PADA PENGUNJUNG AEON MALL BSD CITY - Kusdianto Kusdianto (JMB : Jurnal Manajemen dan Bisnis, 2018)
The purpose of this study is to know and analyze how much influence the brand experience on brand trust and its impact on customer satisfaction of Polo T-Shirt product. Population in this research is every visitor Aeon Mall BSD City met by researcher who was wearing Polo T-Shirt, hence by using unidentified formula obtained by amount of sample counted 100 person. Sampling technique by accidental sampling that anyone who happens to meet can be sampled if it meets the criteria. This research uses an associative-explanatory method. The data used are primary and secondary data. Hypothesis testing is done by using simple linear regression method. Data analysis using statistical data processing software SPSS 22 for Windows. The result of this research shows that brand experience have positive and significant effect to brand trust product of Polo shirt, and brand trust have positive and significant influence to customer satisfaction of Polo T-Shirt product